Frequency of Occupational Health Problems among Farmers of Swat, Peshawar and Kohat Districts Khyber Pakhtunkhwa Pakistan - Naeemullah, Muhammad Jibran Khan, Nadia Khan, Muhammad Ishtiaq, Nizam Muhammad Darwesh, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Agriculture is one of the most dangerous occupations, with high incidence and prevalence of occupational health problems; and farmers are exposed to a too many occupational hazards. Objective: This study was conducted to assess the frequency of occupational health problems among the local farmers of Swat, Peshawar and Kohat Districts Khyber Pakhtunkhwa Pakistan Methodology: After ethical approval; a cross sectional study was conducted among the selected districts of Khyber Pakhtunkhwa; Pakistan. Total of n=325 farmers were assessed regarding the occupational health problems. The famers were selected through convenience sampling technique, based on 95% confidence interval, with 5% precision. A structured open ended questionnaire was used in which farmers were asked regarding the occupational health problems. SPSS version 26.0 was used for data entry and analysis. Finally the result was presented in form of tables. Results: Results showed that 32% were literate; 51.38% had monthly income less than 30000/ PKR; 39.08% had farming for more than 10 years; and 68% were not following personnel protective equipments. Moreover, 38.77% had asthma/COPD; 44.62% had disturbed sleep; 26.77% had hearing loss; 42.15% had eye redness and discharge problems; 64.92% had body ache/ and backache; and 26.77% had history of injuries and falls. Conclusions: It was concluded that farmers revealed a huge list of medical health problems. Moreover, health problems showed relationship with age, educational level, working experience, and compliance of personnel protective equipments and thus occupational education and occupational training strategies were needed to reduce health impacts among farmers.